Feedlot performance, carcass characteristics, and meat characteristics of lambs grown under silvopastoral systems - van Cleef, F. O. S. [UNESP] (2020)
Crossbred lambs were grown under different production systems (unshaded, moderate shading, intense shading) and were submitted to a feedlot finishing period where the performance, efficiency, carcass characteristics, and meat characteristics were evaluated. The dry matter intake was similar among treatments as well as the daily gain and feed efficiency. Hot and cold carcass weights, their dressing percentages, initial and final carcass temperature and pH, as well as initial and final color of meat were unaffected by treatments. In conclusion, the silvopastoral system used during the growing phase neither improved feedlot performance, feed efficiency, nor carcass and meat characteristics of crossbred lambs.